Comparison of portable blood‐warming devices under simulated pre‐hospital conditions: a randomised in‐vitro blood circuit study. (7th May 2019) - Weatherall, A.; Gill, M.; Milligan, J.; Tetlow, C.; Harris, C.; Garner, A.; Lee, A.
Summary: Pre‐hospital transfusion of blood products is a vital component of many advanced pre‐hospital systems. Portable fluid warmers may be utilised to help prevent hypothermia, but the limits defined by manufacturers often do not reflect their clinical use. The primary aim of this randomised in‐vitro study was to assess the warming performance of four portable blood warming devices (Thermal Angel, Hypotherm X LG, °M Warmer, Buddy Lite) against control at different clinically‐relevant flow rates. The secondary aim was to assess haemolysis rates between devices at different flow rates. We assessed each of the four devices and the control, at flow rates of 50 ml.min −1, 100 ml.min −1 and 200 ml.min −1, using a controlled perfusion circuit with multisite temperature monitoring. Free haemoglobin concentration, a marker of haemolysis, was measured at multiple points during each initial study run with spectrophotometry. At all flow rates, the four devices provided superior warming performance compared with the control (p < 0.001). Only the °M Warmer provided a substantial change in temperature at all flow rates (mean (95%CI) temperature change of 21.1 (19.8–22.4) °C, 20.4 (19.1–21.8) °C and 19.4 (17.7–21.1) °C at 50 ml.min −1, 100 ml.min −1 and 200 ml.min −1, respectively). There was no association between warming and haemolysis with any device (p = 0.949) or flow rate (p = 0.169). Practical issues, which may be relevant to clinical use, also emerged during testing. Our results suggest that there were significant differences in the performance of portable blood warming devices used at flow rates encountered in clinical practice.